2017
DOI: 10.1002/cctc.201601575
|View full text |Cite
|
Sign up to set email alerts
|

Water as Cosolvent: Nonviscous Deep Eutectic Solvents for Efficient Lipase‐Catalyzed Esterifications

Abstract: The use of deep eutectic solvent (DES)/water mixtures were explored for the selective enzymatic synthesis of α‐monobenzoate glycerol (α‐MBG) from glycerol and benzoic acid as substrates. Experiments were performed with four DES, three of them containing choline chloride (ChCl), combined with urea (URA), glycerol (GLY), and ethylene glycol (ETA) (in all cases ChCl/HBD 1:2 mol ratio), and another one formed with methylammonium chloride and glycerol (MA/GLY 1:3 mol ratio). The best conversions (99 %) were achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 35 publications
4
63
0
1
Order By: Relevance
“…The high viscosity of DESs is considered to be a hurdle for their application as reaction media. Herein, water can be added to the reaction medium as a cosolvent to significantly lower the viscosity of mixtures of DES/water . Remarkably, a certain amount of water (up to 20 % v / v ) can reduce the viscosity of DESs to the range of water, thus maintaining the nature of DESs as non‐conventional media (i.e., high solubility for hydrophobic substrates) .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The high viscosity of DESs is considered to be a hurdle for their application as reaction media. Herein, water can be added to the reaction medium as a cosolvent to significantly lower the viscosity of mixtures of DES/water . Remarkably, a certain amount of water (up to 20 % v / v ) can reduce the viscosity of DESs to the range of water, thus maintaining the nature of DESs as non‐conventional media (i.e., high solubility for hydrophobic substrates) .…”
Section: Resultssupporting
confidence: 93%
“…A eutectic mixture of ChCl and glycerol (Gly) (1:2 mol mol −1 ), which is also known as glyceline, was selected as a prototypical DES for ADH‐catalyzed reactions. Glyceline is one of the most successfully applied DESs for biocatalysis . MD simulations focus on the quantitative analysis of protein flexibility and hydration level, whereby the results from enzymatic activity and stability are correlated and explained.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…The effects of DESs on activity and stability of lipase were partially correlated with the solvatochromic parameters. For example, the stability of lipase was correlated with hydrogen bond acidity of DESs mixturesKim et al (2016) Thermomyces lanuginosus lipase Pseudozyma antarctica lipase BChCl/U (1:2)ChCl/Gly (1:2)Rapeseed oil and cooking oilBiodieselImproved the additional value of cooking oilKleiner et al (2016)Lipozyme TLIM, Novozym 435ChAc/U (2:1)Glucose with fatty acid vinyl esters; methyl glucoside with fatty acidsGlucose-based fatty acid estersUtilization of combination of ILs and DESsZhao et al (2016)Lipase ASChCl/Gly (1:2)AldehydesNitroalcoholsAddition of water could improve enzyme activity and inhibit DES-catalyzed reactionTian et al (2016) Burkholderia cepacia  lipaseChCl/EG (1:2) p -Nitrophenyl palmitate p -NitrophenolSignificantly improved enzyme activityJuneidi et al (2017)Lipase from ANLChCl/Gly (1:3) Burkholderia cepacia  lipaseDihydromyricetinDihydromyricetin-16-acetateEnhancing substrate solubilityCao et al (2017)iCALBChCl/different sugars (1:1)Fatty acid estersGlycolipidsSugar can serve as HBD and substrateSiebenhaller et al (2017)Lipase GChCl/xylitol (1:1)Glyceryl trioleateEpoxidized vegetable oilsDES stabilized the enzymeZhou et al (2017a)iCALBChCl/Gly (1:2)Benzoic acid and glycerolα-Monobenzoate glycerolWater as co-solvent enzyme remained active in high concentration of DES (92%,v/v)Guajardo et al (2017)PPLChCl/U (1:2)…”
Section: The Application Of Dess In Biocatalysismentioning
confidence: 99%
“…In addition, lipase catalyzed the above reaction with enhancement of 2.6 times in the activity in the presence of choline/ethylene glycol containing 4% water than phosphate buffer (Juneidi et al 2017). Another work has shown that the presence of water is important to increase activity and conversion in a reaction (Guajardo et al 2017). In 2010, Lindberg et al (2010) testified that DESs were beneficial for increasing substrate concentrates and enhancing the regioselectivity of potato epoxide hydrolase.…”
Section: Introductionmentioning
confidence: 99%